APPLICATION OF DESCRIPTIVE STATISTICS METHODS IN CUSTOMS RISK ANALYSIS - O. E. Kudryavtsev; S. E. Tamrazyan (Финансы: теория и практика, 2017)
Improving of risk management’s tools is one of the important ways of increasing the efficiency of customs control. A development of statistical methods to identify potential customs risks is the most promising area of research in this context. The present research is aimed to developing practical proposals for an implementation of descriptive statistics methods for processing information from the customs declarations in order to identify potential risks and to develop customs risk criteria. In the article, a set of the most important parameters of sampling units (goods) based on the adapted regulations of customs statistics methodology is proposed. The sample, which tested the proposed method, is based on a real database of electronic copies of declarations for goods had customs clearance in the region of the Southern Customs Directorate. Sample analysis has shown that the misdeclaration of value is the most typical violation of the Russian customs legislation. A study of descriptive statistics of customs value index for the selected goods led to the conclusion about the potential customs risks of misdeclaration of value and to formulating appropriate risk criteria. The paper deals with additional issues related to customs risk analysis process, including a description of the impact of customs control of goods and a calculation of a potential economic damage. The descriptive statistical methods proposed can be implemented into practice of the customs authorities. The results of the primary data processing can be the basis for classification characteristics for multivariate statistical analysis aimed to a separation of customs declarations array on the areas of high and low risk.